TINGKAT KEPENTINGAN DAN KEPUASAN MASYARAKAT TERHADAP PENGELOLAAN SAMPAH BERBASIS 3R DI PROVINSI ACEH - Alfian Alfian; Eldina Fatimah; Suhendrayatna Suhendrayatna (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2019)
The 3R program is a waste management program that starts from upstream to downstream through reducing, reusing and recycling waste. This study aims to evaluate the success level of 3R based waste management and to identify the level of importance and satisfaction of the community towards the construction of 3R waste treatment facility in Aceh Province. This research uses qualitative method through observation and interview and quantitative method through questionnaire. Evaluation of 3R TPS management activities was conducted through observation and interviews with KSM chairmen based on technical guidance from the Ministry of Public Works and People's Housing (2016). The identification of the level of importance and satisfaction of the community towards the development of 3R TPS facilities is done through the distribution of questionnaires to the local community. Data processing used validity and reliability test, while data analysis used descriptive analysis through Statistical Product and Service Solution (SPSS) v.22 software and biplot analysis through Minitab v.16 software. The results showed that the success rate of 3R based waste management in Aceh Province for west coast area less good with a relative value of 12.30. The capital of the province, the east coast and the central region is good enough with a relative value of 18.20, 17.10 and 17.30 respectively. The level of public interest and satisfaction with the development of the 3R TPS facility for the west coast of the community felt important and dissatisfied with the mean of 4.49 (89.80%) and 2.99 (59.80%), while for the provincial capitals, the east, central and Aceh provinces people felt important and less satisfied with mean importance of 4.45 (89.00%), 4.50 (90.00%), 4.47 (89.40%), 4.48 (89.60%) and mean satisfaction of 3.62 (72.40%), 3.56 (71.20%), 3.27 (65.40%), 3.36 (67.20%).